2011
DOI: 10.1264/jsme2.me10204
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone (FQ) Contamination Does Not Correlate with Occurrence of FQ-Resistant Bacteria in Aquatic Environments of Vietnam and Thailand

Abstract: Fluoroquinolone antibiotics (FQs) have been used worldwide for chemotherapy, animal husbandry, and aquaculture, and the occurrence of FQ-resistant (FQs r ) bacteria in natural environments has been reported. Plasmid-mediated transferable quinolone resistance (PMQR) genes are suspected to originate from the chromosomes of water-dwelling bacteria. However, the occurrence of and the potential reservoir of FQs r bacteria and PMQR genes in aquatic environments have not been elucidated. In this study, we detected FQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 65 publications
3
48
2
Order By: Relevance
“…In the present study, 85.7% of isolates were integron-positive and the detection frequency is much higher than those reported values from previous surface water studies in other regions, for instance, 11% in France (Laroche et al, 2009), 15% in the Czech Republic (Dolejska et al, 2009), 29.6% in Portugal (Henriques et al, 2006), and 65.2% in Chongqing, China (Chen et al, 2010). The results suggest that surface water shows real-time status of contamination as described by Takasu et al (2011). The incidence of integrons in the present study is even higher than those of clinical specimens, such as 40% in Spain (Vinue et al, 2010), 52% in Taiwan (Chang et al, 2000), 59.9% in Shanghai, China (Gu et al, 2008).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In the present study, 85.7% of isolates were integron-positive and the detection frequency is much higher than those reported values from previous surface water studies in other regions, for instance, 11% in France (Laroche et al, 2009), 15% in the Czech Republic (Dolejska et al, 2009), 29.6% in Portugal (Henriques et al, 2006), and 65.2% in Chongqing, China (Chen et al, 2010). The results suggest that surface water shows real-time status of contamination as described by Takasu et al (2011). The incidence of integrons in the present study is even higher than those of clinical specimens, such as 40% in Spain (Vinue et al, 2010), 52% in Taiwan (Chang et al, 2000), 59.9% in Shanghai, China (Gu et al, 2008).…”
Section: Discussioncontrasting
confidence: 65%
“…Previous investigations showed prevalence of antibiotic resistance, integrons and ARGs on surface water in the United States (Storteboom et al, 2010), France (Laroche et al, 2009), Portugal (Henriques et al, 2006), Czech Republic (Dolejska et al, 2009), Korea (Kim et al, 2008), Vietnam (Hoa et al, 2008;Phan et al, 2011;Takasu et al, 2011), Thailand (Takasu et al, 2011), India (Kumar et al, 2010), and Yangtze River, China (Chen et al, 2010). The spreading of multiple resistance bacteria such as E. coli in aquatic environments, especially in drinking water source, is also a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Given no antimicrobials used for therapeutic and prophylactic purpose in these fish ponds, these antibiotics were probably introduced by terrestrial animal wastes containing antibiotics. In integrated fish ponds receiving animal manure in Vietnam, the concentrations of sulfamethoxazole and sulfamethazine were reported in the range of 68.2-625 and 6.78-6662 ng L −1 , respectively [14]; the concentration of norfloxacin was as high as 43.1 ng L −1 , while ciprofloxacin was not observed [30]. The difference of antibiotic concentrations between these above studies and the present study indicated that the concentrations of antibiotics in fish ponds are dependent on the antibiotic consumption and application patterns in different geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Some members of these taxonomic groups belonged to antibiotic resistance bacteria, which have been isolated from aquaculture environment. For example, (fluoro)quinolone-resistant bacteria belonged to diverse taxonomic groups, among which Proteobacteria and Actinobacteria were most abundant in fish ponds [30]. Among sulfamethoxazole-resistant strains from fish ponds, Acinetobacter was the most abundant (35 %), and all of them possessed sulfonamide resistance genes [14], and among oxytetracycline-resistant bacteria from aquaculture sources, one or more tetracycline resistance genes were detected at the percentage of 75 % [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation